2012
DOI: 10.1103/physrevlett.109.025002
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Streamer Discharges from an Isolated Ionization Column at Subbreakdown Conditions

Abstract: This Letter reports a modeling study on the formation of streamer discharges from an isolated ionization column under subbreakdown condition. Numerical simulations show that positive streamers are able to form from the tip of an ionization column in a uniform applied electric field well below the breakdown threshold field. However, even when the applied field approaches the breakdown threshold field, negative streamers fail to originate from the other tip of the ionization column after the positive streamer ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
102
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 24 publications
(30 reference statements)
6
102
0
Order By: Relevance
“…A recently proposed theory suggests that the presence of strong plasma irregularities in the D-region ionosphere is a necessary condition for the initiation of sprite streamers 10,16 , and modelling results show that vertically elongated plasma columns are more favourable for streamer initiation when compared with spherical irregularities 17,18 . The above reconstructed images demonstrate for the first time solid evidence of kilometre-scale plasma irregularities in association with sprite streamer initiation in the D-region ionosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently proposed theory suggests that the presence of strong plasma irregularities in the D-region ionosphere is a necessary condition for the initiation of sprite streamers 10,16 , and modelling results show that vertically elongated plasma columns are more favourable for streamer initiation when compared with spherical irregularities 17,18 . The above reconstructed images demonstrate for the first time solid evidence of kilometre-scale plasma irregularities in association with sprite streamer initiation in the D-region ionosphere.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous modelling studies 11,17,19 , the electron density in plasma irregularities needs to be B2-5 orders of magnitude higher than the ambient electron density to initiate sprite streamers, depending on the onset altitude of the sprite streamers (at lower altitudes, the difference needs to be larger). It is reasonable to believe that such strong perturbations cannot persist in a quiet lower ionosphere, and it is important to emphasize that the origin(s) of those plasma irregularities cannot be determined using the results presented in this work.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of sprite streamers at sub-breakdown conditions was addressed by a few recent modelling studies 21,22,25 . It has been found that streamers can be initiated from thin, dense column ionization patches with a plasma density more than three orders of magnitude, higher than the ambient ionospheric electron density 21,22 or from hundreds of metre wide spherical patches with a density about two orders of magnitude higher than the ambient value 25 .…”
mentioning
confidence: 99%
“…The propagation characteristics of a single sprite streamer, such as acceleration, expansion and brightening, are relatively well understood [10][11][12][13][14][15][16][17][18] . However, how sprite streamers are initiated, a critical question to understand the responses of the upper atmosphere to sudden, strong QE field impacts, is still under active debate 14,[19][20][21][22][23][24][25][26] .…”
mentioning
confidence: 99%
“…Qin et al (2012) showed that the minimum CMC for initiating a positive sprite could be as small as ~200 C km, and vertically elongated inhomogeneity in electron density are found to be more favorable for sprite initiation. Results from simulation work conducted by Liu et al (2012) showed that positive streamers could be initiated from the tip of an ionization column in a uniform applied electric field well below the breakdown threshold field and discussed the importance of inhomogeneities. Studies by Kosar et al (2012) showed that when an appropriate ionization column is introduced, the streamer could be initiated in a variety of electric fields with the lowest electric field of 0.3 E k (E k is the breakdown threshold field).…”
Section: Discussionmentioning
confidence: 99%